Anisotropy in fracture and fatigue resistance of pearlitic steels and its effect on the crack path. (July 2019) - Leitner, T.; Hohenwarter, A.; Pippan, R.
Highlights: The fatigue crack-growth behavior of strongly deformed pearlitic steels was analyzed. A significant orientation dependency with increasing deformation was found. This results from the orientation of the crack in respect to the aligned structure. Crack pattern in rails can be partly explained by the presented results. Abstract: An essential ingredient in the methodology for lifetime estimation is the determination of the crack path. There are several parameters affecting the crack path: the crack driving force and its change with the direction of crack extension, the load mixity, the crack length, the type of yielding (small, large or full scale yielding), static fatigue or environment assisted crack propagation, the microstructure of the material and the anisotropy of fracture resistance. In the present paper, we will focus to the effect of pre-deformation on the fracture resistance, the development of anisotropy, and the resulting crack path during fatigue loading. Special attention will be devoted to the anisotropy of the fracture resistance of fully pearlitic steels, which are typically used for rails. We will focus on the problem of the evolving crack paths in rails and try to answer the question whether the crack paths of head checks are a consequence of the mixed mode loading conditions or if they are related to the anisotropy of the fracture resistance. For that fatigue crack propagation experiments on heavily shear-deformed samples have been performed in different crack orientations with respect to the shear direction. The resulting crack paths were then compared with the crack paths and the deformation structure in rails having been in service. It will be shown that a strong anisotropy in the fracture and fatigue behavior with increasing pre-deformation develops. In addition, the developed anisotropy in pearlitic steels was also compared with the anisotropy and the crack path in other type of heavily shear strained metals and alloys.